Pengukuran status gizi pasien anak menggunakan metode subjective global nutrition assessment (SGNA) sebagai prediktor lama rawat inap, status pulang dan kejadian malnutrisi di rumah sakit - Sri Wahyuni; Madarina Julia; R Dwi Budiningsari (Jurnal Gizi Klinik Indonesia, 2005)
Background: Malnutrition in hospitalized patients is associated with longer stay, higher risk of complication and mortality.Subjective Global Nutrition Assessment (SGNA) is a recently discovered method to assess nutritional status.Objective: To assess the association between nutritional statuses of under-fi ve year old patients measured with SGNA and length of inpatient stay, discharge status and occurrence of malnutrition.Methods: Under-fi ve year old patients hospitalized in Pediatric Ward of Pekanbaru Hospital had their nutritional status measured with SGNA on admission. Three groups were identifi ed: exposed to bad nutritional status, i.e. SGNA C (worst) and B (moderate), and not exposed to bad nutritional status (SGNA A). Length of hospital stay, discharge status and occurrence of malnutrition in exposed groups (SGNA B and C) were independently compared to non-exposed group (SGNA A) as the reference. Other variables measured were types of diseaseand intake of energy and protein.Results: Children with SGNA C and B had higher risk to stay longer in hospital, i.e. RR (95%CI) of 3.2 (1.7-6.0) and 2.5 (1.3 – 4.9), respectively. They had also higher risk for discharged without complete recovery, i.e. RR (95%CI) of 3.3 (1.8-6.2) and 2.2 (1.1 – 4.3), respectively. Children with SGNA C had higher risk for hospital malnutrition, i.e. RR (95%CI) of 2.8 (1.5-5.2), but not children with SGNA B. Types of disease, energy and protein intake were not important effect modifi ers for this association.Conclusion: Nutritional status on admission was signifi cantly associated with length of hospital stay, discharge status and occurrence of hospital malnutrition.